Genomic characterization of intracranial teratomas using whole genome sequencing - Zhang, Chao; Zhou, Xiaoyu; Huang, Xiang; Ding, Xinghua; Wang, Yang; Zhang, Rong (Frontiers in Oncology, 2022)
Background: Intracranial teratoma is a rare neoplasm of the central nervous system, often classified into mature and immature types and occurs mainly in children and adolescents. To date, there has been no comprehensive genomic characterization analysis of teratoma due to its rarity of the cases. Methods: Forty-six patients with intracranial teratomas were collected and 22 of them underwent whole-exome sequencing, including 8 mature teratomas and 14 immature teratomas. A comprehensive analysis was performed to analyze somatic mutations, copy number variants (CNVs), mutational signatures, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway in our cohort. Results: The most common somatic mutated gene in intracranial teratomas was CARD11 (18%) and IRS1 (18%), followed by PSMD11, RELN, RRAS2, SMC1A, SYNE1 and ZFHX3, with mutation rates of 14% for the latter six genes. Copy number variation was dominated by amplification, among which ARAF (50%), ATP2B3 (41%), GATA1 (41%), ATP6AP1 (36%), CCND2 (36%) and ZMYM3 (36%) were the most frequently amplified genes. Copy number deletion of SETDB2 and IL2 only appeared in immature teratoma (43% and 36%, respectively), but not in mature teratoma (p = 0.051 and 0.115, respectively). Prognostic analysis showed that TP53 mutations might be associated with poor prognosis of intracranial teratomas patients. Conclusions: Our study revealed the genetic characteristics of intracranial teratoma which might be valuable for guiding future targeted therapies.